Biofilm Compositions and Bacterial Diversity on Kitchen Towels in Daily Use - Yao Zhang; Kexin Li; Yibo Ru; Yue Ma (Microorganisms)
Towels with complex woven structures are susceptible to biofilm formation during daily use. The composition of biofilms formed on towels used under real-life conditions has yet to be studied. Thus, we investigated the color changes, structural integrity, and biofilm development on towels used continuously for 10 weeks by 12 volunteers in specific kitchen environments. Apparent biofilms composed of bacteria and extracellular polymeric substances (EPSs) were found on all used towels. The bacteria concentrations ranged from 4 to 7 log CFU/g. Proteins were the most abundant EPS, followed by polysaccharides and eDNA. A high-throughput sequencing method was employed to investigate the bacterial diversity on the towels. The predominant bacterial genera differed from towel to towel. Kocuria, Rothia, Psychrobacter, Enhydrobacter, and Pseudomonas are genera of relatively high abundance that may originate from the human body and foods. In addition, correlations among environmental factors, major bacterial genera, physical properties, and biofilm formation of the towels were analyzed, which could provide a scientific reference for maintaining towel hygiene.